Factors Influencing The Outcome Of Severe Pneumonia Among Children Having Age From 2 Months To 5 Years In A Tertiary Healthcare Hospital: Factors Influencing the Outcome of Severe Pneumonia - Iqbal, Noureen; Zafar, Farhana; Iqbal, Mohammad (Pakistan Journal of Health Sciences, 2023)
One of the leading causes of high rate of morbidity and mortality among pediatrics under the age of five years is pneumonia. A report of WHO published in 2013 stated that pneumonia is accountable for about one hundred and twenty million patients each year and the most vulnerable are developing countries. Objective: To find out the rate of occurrence of different factors and pneumonia’s outcome among children having age from two months to five years in tertiary healthcare hospital. Methods: It was carried out at ICU of Pediatric Department of Ziauddin Hospital Karachi, from June 2021 to December 2021. It included 145 patients under the inclusion standard. Results: Average weight, height, age and duration of hospitalization in this research work was 7.72 ± 3.87 kilograms, 68.23 ± 15.28 centimeters, 8.72 ± 4.24 years and 8.72 ± 4.24 days. Total were 63.40% (n: 92) male and 36.60% (n: 53) female patients. out of total 145 patients, 27.60, 73.10, 29.70, 38.60, 35.20, 40.0 and 7.60% patients had mechanical ventilation’s requirement, delayed hospitalization, URTI history in family, mostly suffered children suffered from pneumonia in less than 2.5yrs of age. And regarding outcome, prolonged hospital stay, mechanical ventilation and mortality has significant association with younger age. Conclusions: It was concluded that association can cause the improvement in the management strategies and possibility of the survival for the children suffering from pneumonia. So, there is need of close monitoring of all the patients with consistent follow up visits.